(untitled) (Journal of the Bangladesh Agricultural University, 2016)
A study was conducted to assess the level of Cr, Pb, Cd, Ni, Zn, Cu, Fe and Mn contamination in the sediment samples of the Buriganga river, at the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh. Total 14 sediment samples were collected from different areas of upstream of the Buriganga river. The mean concentrations of total Cr, Pb, Cd, Ni, Fe, Cu, Zn and Mn in the sediment samples were 173.4, 31.4, 1.5, 153.3, 481.8, 344.2, 12989 and 4036 ?g g-1, respectively. The range of pH and EC of sediment were 5.87-8.21 and 230-707 ?S cm-1, respectively. The mean value of organic matter in sediment samples was 13.4%. Heavy metal concentrations in sediment were compared with geochemical background and standard values, previous report on the Buriganga river and other rivers in Bangladesh. The average concentration of Cr, Pb and Ni in sediments of the Buriganga river is almost twice of the geochemical background i.e. average worldwide shale standard and continental upper crust value, Cd and Zn is about five times and Cu content is about ten times higher than the geochemical background values. Average concentration of Cr, Cu and Ni exceeded the severe effect level (SEL) values, where as Pb, Cd and Zn exceeded toxicity reference values (TRV). However, the concentration of heavy metal in the sediment samples of the Buriganga river for the year 2009 of the same river reported by corresponding author was relatively higher than this study average. The average Enrichment factors (EFc) for Zn, Cu, Mn and Cd reflects extremely contaminated pollution level which implies that these metals originated from point source of pollution and very severely enriched in river sediments. The pollution load index (PLI) of sediments of the studied region varied from 1.61-7.51. The geoaccumulation index (Igeo) for Cu of five locations was greater than 3.0, which exhibited strongly polluted sediment quality. The Igeo for Mn in 11 locations and Zn in 12 sites were greater than 1.0, indicated moderately polluted sediment quality. Heavy metal pollution intensity in the Buriganga river water and sediments signaled alarming condition for city dwellers and aquatic ecosystem of the river. Sustainable steps and continuous monitoring on pollution prevention and cleanup operation is suggested to minimize pollution. J. Bangladesh Agril. Univ. 13(2): 229-238, December 2015